Endovascular recanalization of symptomatic non-acute occlusion of the vertebrobasilar artery - Zhou, ZhiLong; Li, TianXiao; Zhu, LiangFu; Wu, LiHeng; Guan, Min; Ma, ZhenKai; Liu, YangHui; Qin, Jin; Gao, BuLang (Frontiers in Neurology, 2023)
Purpose The study aimed to investigate the safety, effect, and risk factors of endovascular recanalization of symptomatic non-acute occlusion of the vertebrobasilar artery (SNOVA). Materials and methods Patients with SNOVA were retrospectively enrolled and treated with endovascular recanalization. The clinical data, endovascular treatment, peri-procedural complications, and follow-up outcomes were analyzed. Results A total of 88 patients were enrolled, with an interval to recanalization of 2–89 days (median 23) and an mRS of 2–5 (median 3 and IQR 1). Occlusion was in the intracranial vertebral artery in 68 (77.27%) patients and basilar artery in 20 (22.73%), with an occlusion length of 4.5–43.7 mm (mean 18.3 ± 8.8). Endovascular recanalization was successful in 81 (92.0%) patients. Post-dilatation was performed in 23 (28.4%) patients. After stenting, the residual stenosis was 10%–40% (mean 20.2% ± 7.6%). Peri-procedural complications occurred in 17 (19.3%) patients, with a mortality rate of 5.7%. In total, 79 (95.18%) patients underwent follow-up 5–29 (mean 16.9 ± 5.5) months later, with an mRS score of 0–6 (median 1 and IQR 1) at follow-up, being significantly (p < 0.0001) better than that at discharge. Stroke occurred in 9 patients (11.4%) in 1 year. In-stent restenosis occurred in 19 (25.33%) patients. Significant (p < 0.05) independent risk factors were blunt occlusion for successful recanalization, duration to recanalization and blunt occlusion for peri-procedural complications, and post-dilatation for both in-stent restenosis and 1-year stroke or death events. Conclusion Endovascular recanalization of symptomatic non-acute occlusion of the vertebrobasilar artery is feasible even for a long occlusion segment, with a high recanalization rate, a low complication rate, and a good prognosis. Blunt occlusion and duration from the onset to recanalization may affect successful recanalization and peri-procedural complications while post-dilatation may affect in-stent restenosis and prognosis.